State Power Limitations on Religion for The Fulfillment of The Constitutional Rights of Indigenous Religion Believers in Indonesia - Jufri, Muwaffiq; Raphael D. Jackson-Ortiz; Putra Perdana Ahmad Saifulloh; Evis Garunja; Sonia Ivana Barus (CV. Pustaka Parawali, 2024)
This article examines the importance of state power in regulating religion in a limited scope. This is intended to solve classic problems, such as the state immediately fulfilling the constitutional rights of local religious adherents. Even though the Constitutional Court partially recognizes the existence of local religions through decision No.97/PUU-XIV/2016, this decision does not change the legal status of local religions, which are not considered official state religions. This research contributes to efforts to fulfill the right to freedom of religion for followers of Indigenous religions through policy design that does not restrict local religions from becoming official state religions. This study employed a normative legal research method, which concludes that the state's involvement in limiting local religions is by issuing various rules that distinguish religion from belief and standardizing religion, which closes the opportunity for local religions to be recognized as an official state religion. Limitations on state power can be carried out by issuing state regulations in religion, which limits to regulate fostering harmony of religious life and upholding the freedom of religion and avoiding regulatory patterns that classify religions and standardize religion because it will hinder the fulfilment of the constitutional rights of belief adherents